Robust cooperative distributed MPC: A multi-model approach. (September 2022) - Sencio, Rafael R.; Odloak, Darci
Abstract: In this work, we propose a robust cooperative distributed MPC based on a multi-model approach. A new method for obtaining a state-space model in the velocity-form of inputs is presented. This model is suitable for predicting steady-state outputs within an offset-free setpoint tracking framework in which a terminal constraint is relaxed to guarantee problem feasibility under any setpoint change. The proposed strategy also deals with the zone control problem, which is widely applied in the process industry. Moreover, an alternative algorithm is proposed in order to improve convergence over iterations. Recursive feasibility, convergence and stability properties are proved. Two numerical examples are provided with the application of the proposed algorithms. Highlights: A robust cooperative distributed MPC based on a multi-model approach is presented. The proposed strategy is suitable for offset-free setpoint tracking and zone control. An alternative algorithm to improve convergence over iterations is proposed. Recursive feasibility, convergence and stability properties are proved.